2013
DOI: 10.1016/j.biopsych.2013.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Lobe γ-Aminobutyric Acid Levels During Adolescence: Associations with Impulsivity and Response Inhibition

Abstract: Background The brain undergoes major remodeling during adolescence, resulting in improved cognitive control and decision-making, and reduced impulsivity, components of behavior mediated in part by the maturing frontal lobe. Gamma-amino butyric acid (GABA), the main inhibitory neurotransmitter system, also matures during adolescence, with frontal lobe GABA receptors reaching adult levels late in adolescence. Thus, the objective of this study was to characterize in vivo developmental differences in brain GABA le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
155
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(163 citation statements)
references
References 84 publications
6
155
2
Order By: Relevance
“…Whilst GABA measured this way is predominantly metabolic in origin (Myers et al 2014; Myers et al 2016b), it is interesting that a lowered magnetic resonance spectroscopy GABA signal ([GABA+]) in HV has in some studies been associated with higher levels of impulsivity. For instance, it has been shown that [GABA+] levels in dorsolateral prefrontal regions negatively correlate with urgency impulsivity (Boy et al 2011); low [GABA+] in perigenual anterior cingulate cortex was associated with greater delay aversion on Cambridge gambling task (Fujihara et al 2015) and higher scores on self‐report Barratt Impulsiveness Scale‐11 in one study (Silveri et al 2013) but not another (Janes et al 2013). Lower [GABA+] in the striatum is associated with poorer impulse control in Go‐NoGo task (Quetscher et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst GABA measured this way is predominantly metabolic in origin (Myers et al 2014; Myers et al 2016b), it is interesting that a lowered magnetic resonance spectroscopy GABA signal ([GABA+]) in HV has in some studies been associated with higher levels of impulsivity. For instance, it has been shown that [GABA+] levels in dorsolateral prefrontal regions negatively correlate with urgency impulsivity (Boy et al 2011); low [GABA+] in perigenual anterior cingulate cortex was associated with greater delay aversion on Cambridge gambling task (Fujihara et al 2015) and higher scores on self‐report Barratt Impulsiveness Scale‐11 in one study (Silveri et al 2013) but not another (Janes et al 2013). Lower [GABA+] in the striatum is associated with poorer impulse control in Go‐NoGo task (Quetscher et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…GABAergic projections have been less well investigated in the context of addiction although GABAergic mechanisms influence function of the mesolimbic pathway [58]. While GABAergic manipulation was successful in modulating response impulsivity in rodents, in humans, GABAergic function has been arguably linked more closely to self-report impulsivity and impulsive choice [5961] than to response impulsivity (although see [62]). Within the mesolimbic pathway, dopamine and serotonin have been the two most heavily studied neurotransmitters with regard to impulsivity.…”
Section: Underlying Neurocircuitry Of Impulsivitiesmentioning
confidence: 99%
“…In a study of children with ADHD, lower GABA levels in a region including parts of the primary somatosensory and motor cortices have been reported (Edden et al, 2012). In healthy adolescents and adults, two recent studies showed a negative association of GABA levels in the dorsolateral prefrontal cortex with impulsivity (Boy et al, 2011;Silveri et al, 2013). Despite these studies, Hayes argues that there is still a lack of research on GABA in the general context of impulsivity (Hayes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%